2020
DOI: 10.1029/2020jb019566
|View full text |Cite
|
Sign up to set email alerts
|

Isotropic and Anisotropic P Wave Velocity Structures of the Crust and Uppermost Mantle Beneath Turkey

Abstract: Compressional and extensional tectonics following northward plate convergences since the Miocene have formed the major surface features in Turkey, such as faulting and orogeny. Despite increasing efforts in last few decades aiming to elucidate the current architecture of the crust and mantle beneath Turkey, several issues regarding the depth extent of the deformation zones, crust-mantle interaction (e.g., coupling and decoupling) in relation to the deformation, and stress transmission in the lithosphere remain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
16
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 137 publications
(225 reference statements)
3
16
0
Order By: Relevance
“…Given the evidence for a thinned lithosphere, the apparent lack of influence of either the NAF or EAF on upper mantle anisotropy, and the discrepancy between plate motion and anisotropic fast directions, it has been suggested that the Anatolian crust and mantle are mechanically decoupled (Mutlu & Karabulut, 2011;L. Jolivet et al, 2013;Wang et al, 2020). On the other hand, low-velocity upper mantle structures beneath the NAF have been imaged in tomographic studies and interpreted as signatures of a plate-scale shear zone (Fichtner et al, 2013;Papaleo et al, 2017Papaleo et al, , 2018, favoring a hypothesis of coherent crust and lithospheric mantle deformation.…”
Section: Accepted Articlementioning
confidence: 99%
See 3 more Smart Citations
“…Given the evidence for a thinned lithosphere, the apparent lack of influence of either the NAF or EAF on upper mantle anisotropy, and the discrepancy between plate motion and anisotropic fast directions, it has been suggested that the Anatolian crust and mantle are mechanically decoupled (Mutlu & Karabulut, 2011;L. Jolivet et al, 2013;Wang et al, 2020). On the other hand, low-velocity upper mantle structures beneath the NAF have been imaged in tomographic studies and interpreted as signatures of a plate-scale shear zone (Fichtner et al, 2013;Papaleo et al, 2017Papaleo et al, , 2018, favoring a hypothesis of coherent crust and lithospheric mantle deformation.…”
Section: Accepted Articlementioning
confidence: 99%
“…At the NAF, in addition to the lack of fault‐parallel ϕ observations in the aforementioned XKS splitting studies (Figure 2a), fault‐oblique uppermost mantle anisotropic fast directions have been observed in anisotropic Pn tomography (Mutlu & Karabulut, 2011), as has a sharp change in fast directions across the Moho in anisotropic P ‐wave tomography (Wang et al., 2020). Given the evidence for a thinned lithosphere, the apparent lack of influence of either the NAF or EAF on upper mantle anisotropy, and the discrepancy between plate motion and anisotropic fast directions, it has been suggested that the Anatolian crust and mantle are mechanically decoupled (L. Jolivet et al., 2013; Mutlu & Karabulut, 2011; Wang et al., 2020). On the other hand, low‐velocity upper mantle structures beneath the NAF have been imaged in tomographic studies and interpreted as signatures of a plate‐scale shear zone (Fichtner et al., 2013; Papaleo et al., 2017, 2018), favoring a hypothesis of coherent crust and lithospheric mantle deformation.…”
Section: Introductionmentioning
confidence: 96%
See 2 more Smart Citations
“… Tectonic sketch map of the study region (adapted from Wang et al., 2020). The red lines indicate major faults and trenches while suture zones are represented by thick black lines based on Okay and Tüysüz (1999).…”
Section: Introductionmentioning
confidence: 99%